Evaluation of the Effectiveness of a Musical Cognitive Restructuring App for Black Inner-City Girls: Survey, Usage, and Focus Group Evaluation - Neal-Barnett, Angela; Stadulis, Robert; Ellzey, Delilah; Jean, Elizabeth; Rowell, Tiffany; Somerville, Keaton; Petitti, Kallie; Siglow, Benjamin; Ruttan, Arden; Hogue, Mary (JMIR Publications, 2019)
BackgroundResearch on mobile health (mHealth) app use during adolescence is growing; however, little attention has been paid to black adolescents, particularly black girls, who are generally underresearched and underserved in psychological intervention research. Cognitive restructuring is an important tool in anxiety and fear management and involves two parts: (1) recognizing and deconstructing erroneous thoughts and (2) replacing negative anxiety and stress-provoking thoughts with positive thoughts. In our work with black adolescent females, we found that cognitive restructuring is a difficult skill to practice on one's own. Thus, drawing upon the importance of music in the black community, we developed the Build Your Own Theme Song (BYOTS) app to deliver a musical form of the technique to middle-school black girls. ObjectiveOur aim in this mixed methods study is to evaluate the effectiveness of the BYOTS app. We hypothesize that participants will expect the app to be effective in reducing negative thoughts and that the app will meet their expectations and data generated from the app will demonstrate a reduction in negative thinking and anxiety. MethodsA total of 72 black or biracial seventh- and eighth-grade adolescent females were enrolled in Sisters United Now (SUN), an eight-session culturally infused and app-augmented stress and anxiety sister circle intervention. Before using the BYOTS app, girls completed the Multidimensional Anxiety Scale for Children 2 and the App Expectations Survey. Usage data collected from the app included an assessment of negative thinking before and after listening to their song. After completion of the intervention, focus groups were held to gather qualitative data on participants' app experience. ResultsResults using paired sample t tests indicated negative thinking was significantly lower at day 7 than day 1 (t31=1.69, P=.05). Anxiety from preuse to postuse of the app was also reduced (t38=2.82, P=.004). Four effectiveness themes emerged from the focus groups: difference in behavior and temperament, promoted calmness, helpfulness in stressful home situations, and focused thinking via the SUN theme song. ConclusionsThe BYOTS app is a useful tool for delivering musical cognitive restructuring to reduce negative thinking and anxiety in an underserved urban population. Changes were supported both quantitatively and qualitatively. Participants, their peers, and their family noted the difference. Findings support expanding the research to black girls of various socioeconomic statuses and geographic diversity. Currently, the app augments SUN, a culturally relevant intervention. Future research will explore BYOTS as a stand-alone app.